2012
DOI: 10.1161/circgenetics.111.961888
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing to Identify a Novel Gene (Caveolin-1) Associated With Human Pulmonary Arterial Hypertension

Abstract: Background Heritable and idiopathic pulmonary arterial hypertension (PAH) are phenotypically identical and associated with mutations in several genes related to TGF beta signaling, including bone morphogenetic protein receptor type 2 (BMPR2), activin receptor-like kinase 1 (ALK1), endoglin (ENG), and mothers against decapentaplegic 9 (SMAD9). Approximately 25% of heritable cases lack identifiable mutations in any of these genes. Methods and Results We used whole exome sequencing to study a three generation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
304
1
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(319 citation statements)
references
References 30 publications
4
304
1
10
Order By: Relevance
“…Cav1-null mice were viable and fertile, but displayed various phenotypes, including abnormal regulation of lipid metabolism and impaired nitric oxide and calcium signaling, which led to aberrant regulation of myogenic tone in the cardiovascular system (Drab et al 2001) and impaired liver regeneration after injury (Fernandez et al 2006). On the basis of these observations, homozygotic or heterozygotic mutations in the CAV1 gene have been identified in patients with congenital generalized lipodystrophy type 3 (CGL3) (Kim et al 2008), partial lipodystrophy, congenital cataracts, neurodegeneration syndrome (LCCNS) (Cao et al 2008), and primary pulmonary hypertension 3 (PPH3) (Austin et al 2012). Comparing the clinical features of these syndromes with those of patients who received long-term glucocorticoid therapy indicates that, in addition to muscle wasting and insulin resistance, clinical manifestations such as cataracts, progressive loss of adipose tissue, and hypertension might be caused by glucocorticoid-induced downregulation of Cav1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Cav1-null mice were viable and fertile, but displayed various phenotypes, including abnormal regulation of lipid metabolism and impaired nitric oxide and calcium signaling, which led to aberrant regulation of myogenic tone in the cardiovascular system (Drab et al 2001) and impaired liver regeneration after injury (Fernandez et al 2006). On the basis of these observations, homozygotic or heterozygotic mutations in the CAV1 gene have been identified in patients with congenital generalized lipodystrophy type 3 (CGL3) (Kim et al 2008), partial lipodystrophy, congenital cataracts, neurodegeneration syndrome (LCCNS) (Cao et al 2008), and primary pulmonary hypertension 3 (PPH3) (Austin et al 2012). Comparing the clinical features of these syndromes with those of patients who received long-term glucocorticoid therapy indicates that, in addition to muscle wasting and insulin resistance, clinical manifestations such as cataracts, progressive loss of adipose tissue, and hypertension might be caused by glucocorticoid-induced downregulation of Cav1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, reduction in the endothelial caveolin-1 protein and mRNA has been observed in patients with idiopathic PAH (2, 39). Austin et al (6) recently reported caveolin-1 mutation associated with PAH. The expression of the endothelial caveolin-1 was reduced in these cases.…”
Section: Disruption Of Ec Membranementioning
confidence: 99%
“…HPAH accounts for approximately 6% of PAH cases and has an autosomal-dominant mode of inheritance originally associated with mutations in bone morphogenetic protein receptor type 2 (BMPR2) gene (5,6), although there are less frequent associations with germline mutations in activin receptor-like kinase type 1 (ACVRL1), endoglin (ENG, reviewed in [7]), the SMAD gene family of proteins (8), and recently in caveolin-1 (CAV1 [9]) and in the potassium channel subfamily K, member 3 (KCNK3 [10]). Idiopathic PAH includes cases with no clear cause, although the role for underlying mutations in BMPR2 in 5-25% of cases has been recently appreciated (7,11).…”
mentioning
confidence: 99%
“…Our investigation of the prostacyclin synthase (PGIS; official gene symbol PTGIS) DNA promoter sequence variants reveals a complexity of sequence polymorphisms within a short region (z525 base pairs [bp]) encompassing the minimum promoter (231 bp, a CpG island), exon 1, ; green bars) and a 9-base variable number of tandem repeats (VNTR) with three to nine copies of the tandem repeat (red arrows). SNPs 1, 2, and 3 along with the sequence numbering were previously described (9). and the 59 side of intron 1 (12).…”
mentioning
confidence: 99%